Trade openness and youth unemployment in sub-Saharan Africa: The role of gender and institutional quality - Bernardin Senadza; Raymond Kofitse Sosu; Emmanuel Kwasi Zewu (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2024)
Purpose: This paper examines the effect of trade openness on youth employment in Sub-Saharan Africa, incorporating the roles of institutional quality and gender. Design/methodology/approach: The study employs the random effects estimator using a panel data of 35 Sub-Saharan African countries from 2000 to 2020. Findings: The study finds that trade openness has a negative and significant effect on youth unemployment, with a stronger effect on female youth. Labour market institutions, measured by the Fraser Institute's Economic Freedom of the World index, play a key role in reducing youth unemployment, with a more pronounced effect on female youth. However, the interaction of institutions with trade openness reveals that trade openness worsens youth unemployment in countries with stronger labour market institutions. Research limitations/implications: The findings highlight the need to enhance the competitiveness and export capacity of trade sectors to create more jobs. This, however, should be implemented in conjunction with policies that encourage youth employment with no or little distortion to the labour market. Originality/value: This study contributes to the literature by examining how institutions and gender shape the trade openness-youth unemployment nexus in SSA.
Keywords: F1; F11; F16; J16; 330; Trade openness; youth unemployment; institutions; random effects model; Sub-Saharan Africa